Bacterial Metabolic Response to Change in Phytoplankton Communities and Resultant Effects on Carbon Cycles in the Amundsen Sea Polynya, Antarctica - Kim, Bomina; Kim, Sung-Han; Min, Jun-Oh; Lee, Youngju; Jung, Jinyoung; Kim, Tae-Wan; Lee, Jae Seong; Yang, Eun Jin; Park, Jisoo; Lee, SangHoon; Hyun, Jung-Ho (Frontiers in Marine Science, 2022)
We investigated changes in heterotrophic bacterial metabolic activities and associated carbon cycles in response to a shift in dominant phytoplankton communities during two contrasting oceanographic conditions in austral summer in the Amundsen Sea polynya (ASP), Antarctica: the closed polynya condition in 2014 (ANA04) and the open polynya condition in 2016 (ANA06). In ANA04, Phaeocystis antarctica predominated phytoplankton biomass, comprising 78% of total phytoplankton carbon biomass, whereas diatoms and Dictyocha speculum accounted for 45% and 48% of total phytoplankton carbon biomass, respectively, in ANA06. Bacterial production (BP) was significantly correlated with only chlorophyll-a (Chl-a, rho = 0.66, p < 0.001) in P. antarctica-dominated ANA04, whereas there were significant positive relationships of BP with various organic carbon pools, such as chromophoric dissolved organic matter (CDOM, rho = 0.84, p < 0.001), Chl-a (rho = 0.59, p < 0.001), and dissolved organic carbon (DOC, rho = 0.51, p = 0.001), in ANA06 when diatoms and D. speculum co-dominated. These results indicate that BP depended more on DOC directly released from P. antarctica in ANA04, but was supported by DOC derived from various food web processes in the diatom-dominated system in ANA06. The BP to primary production (BP:PP) ratio was three-fold higher in P. antarctica-dominated ANA04 (BP:PP = 0.09), than in diatom- and D. speculum-co-dominated ANA06 (BP:PP = 0.03). These results suggested that the microbial loop is more significant in Phaeocystis-dominated conditions than in diatom-dominated conditions. In addition, the decreases in BP:PP ratio and bacterial respiration with increasing diatom proportion in the surface mixed layer indicated that the shift from P. antarctica to diatom predominance enhanced biological carbon pump function by increasing particulate organic carbon export efficiency. Consequently, our results suggest that bacterial metabolic response to shifts in phytoplankton communities related to climate change could ultimately affect larger-scale ecological and biogeochemical processes in the water column of the ASP.